The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1108/ijbpa-09-2023-0127
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption and carbon emission of conventional and green buildings using building information modelling (BIM)

Elijah Kusi,
Isaac Boateng,
Humphrey Danso

Abstract: PurposeUsing building information modelling (BIM) technology, a conventional structure in this study was converted into a green building to measure its energy usage and CO2 emissions.Design/methodology/approachDigital images of the existing building conditions were captured using unmanned aerial vehicle (UAV), and were fed into Meshroom to generate the building’s geometry for 3D parametric model development. The model for the existing conventional building was created and converted to an energy model and expor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Augmented reality is also being explored in combination with BIM, as Al-Dhaimesh et al [10] examined its benefits in the design process of the AEC industry. Other studies have shown the potential for BIM to benefit infrastructure time-cost analysis [11], minimize cost overruns in railway projects [12], transform traditional buildings into green buildings [13], and even aid in the design and manufacturing of prefabricated bridges [14]. While BIM has proven effective in solving problems across a wide range of projects, it is important to note that obstacles to its use can vary by country and project.…”
Section: Introductionmentioning
confidence: 99%
“…Augmented reality is also being explored in combination with BIM, as Al-Dhaimesh et al [10] examined its benefits in the design process of the AEC industry. Other studies have shown the potential for BIM to benefit infrastructure time-cost analysis [11], minimize cost overruns in railway projects [12], transform traditional buildings into green buildings [13], and even aid in the design and manufacturing of prefabricated bridges [14]. While BIM has proven effective in solving problems across a wide range of projects, it is important to note that obstacles to its use can vary by country and project.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a 3.5% reduction in energy intensity, overall energy demand and emissions rose by about 1% from 2021 [8]. Another feature is that high emissions from the production of building materials and building construction also potentially contribute to global warming [6,9,10], about 21% of global greenhouse gas emissions [8].…”
Section: Introductionmentioning
confidence: 99%